Incidence, clinical features, risk factors, and outcomes of Intraocular inflammation following Brolucizumab in Indian eyes – A multicentric study - Debdulal Chakraborty; Soumen Mondal; Sabyasachi Sengupta; Zahir Abbas; Khushboo Chandra; Subhendu Boral; Aniruddha Maiti; Sangeeta Roy; Angshuman Mukherjee; Arnab Das; Somnath Chakraborty; Pinaki Nag (Indian Journal of Ophthalmology, 2023)
Purpose: To report the incidence, clinical features, potential risk factors, and outcomes of intraocular inflammation (IOI) following brolucizumab in Indian eyes. Methods: All consecutive patients diagnosed with brolucizumab-induced IOI from 10 centers in eastern India between October 2020 and April 2022 were included. Results: Of 758 injections given during the study period across centers, 13 IOI events (1.7%) were recorded attributable to brolucizumab. The IOI occurred after the first dose in two eyes (15%) (median 45 days after brolucizumab), second dose in six eyes (46%) (median = 8.5 days), and third dose (39%) in the remaining five eyes (median 7 days). Reinjections of brolucizumab were administered at a median interval of 6 weeks (interquartile range = 4–10 weeks) in the 11 eyes, where IOI occurred after the second or third dose. Eyes that experienced IOI after the third dose had received a significantly greater number of previous antivascular endothelial growth factor injections (median = 8) compared to those who developed it after the first or second dose (median = 4) (P = 0.001). Anterior chamber cells were seen in almost all eyes (n = 11, 85%), while peripheral retinal hemorrhages were seen in two eyes, and one eye showed branch artery occlusion. Two-thirds of patients (n = 8, 62%) recovered with a combination of topical and oral steroids, while remaining recovered with topical steroids alone. Irreversible visual loss was not seen in any eye, and median vision recovered to pre-IOI levels by 3 months' time point. Conclusion: Brolucizumab-induced IOI was relatively rare, occurring in 1.7% of eyes, was more common after the second or third injection, especially in those who required frequent reinjections every 6 weeks, and occurred earlier with increasing number of previous brolucizumab injections. Continued surveillance is necessary even after repeated doses of brolucizumab.